2022
DOI: 10.1038/s42003-022-04360-2
|View full text |Cite
|
Sign up to set email alerts
|

FANCD2 promotes mitotic rescue from transcription-mediated replication stress in SETX-deficient cancer cells

Abstract: Replication stress (RS) is a leading cause of genome instability and cancer development. A substantial source of endogenous RS originates from the encounter between the transcription and replication machineries operating on the same DNA template. This occurs predominantly under specific contexts, such as oncogene activation, metabolic stress, or a deficiency in proteins that specifically act to prevent or resolve those transcription-replication conflicts (TRCs). One such protein is Senataxin (SETX), an RNA:DNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 77 publications
0
5
0
Order By: Relevance
“…In addition, reactive oxygen species (ROS) were recently shown to induce replicative stress by enhancing replicationtranscription conflicts and R-loop formation (30). Moreover, the group of Valeria Naim identified Senataxin (SETX), an RNA:DNA helicase involved in the resolution of R-loops, as a factor protecting cells from transcription-associated replication stress (31). Collectively, the aforementioned studies confirmed the existing causes of replicative stress and enabled us to comprehend their underlying mechanisms.…”
Section: Recent Developments In Replication Stressmentioning
confidence: 88%
“…In addition, reactive oxygen species (ROS) were recently shown to induce replicative stress by enhancing replicationtranscription conflicts and R-loop formation (30). Moreover, the group of Valeria Naim identified Senataxin (SETX), an RNA:DNA helicase involved in the resolution of R-loops, as a factor protecting cells from transcription-associated replication stress (31). Collectively, the aforementioned studies confirmed the existing causes of replicative stress and enabled us to comprehend their underlying mechanisms.…”
Section: Recent Developments In Replication Stressmentioning
confidence: 88%
“…Genomic Instability . Replicative stress incurs DNA damage in the form of chromosomal aberrations and DSBs that attenuate replicative lifespan of cells and induce aging-associated tissue dysfunction 9 , 121 , 123 . Telomere Attrition .…”
Section: Hallmarks Of Aging Driven By Replication Stressmentioning
confidence: 99%
“…DSB formation is also incurred by replication fork blockage imposed by transcription-replication conflicts, and this DNA damage induction is enhanced in the presence of co-occurring three-stranded DNA-RNA hybrids with the associated non-template ssDNA (R-loops) that exacerbate replication fork stalling 120 . R-loop persistence in mitosis resulting from depletion of the R-loop resolving helicase senataxin (SETX) has also been shown to induce chromosomal fragility and DNA under-replication 121 . Deficiency in the SETX-interacting factor senataxin-associated exonuclease 1 (San1) induces early onset murine cardiomyopathy associated with elevated cardiomyocyte R-loop and DSB levels, evidencing the role of replication stress-induced DNA damage accrual in premature induction of age-related pathologies 122 .…”
Section: Hallmarks Of Aging Driven By Replication Stressmentioning
confidence: 99%
“…R-loop accumulation upon Sen1/SETX deficiency was subsequently confirmed genome-wide in yeast and human cells ( Chan et al 2014 ; Costantino and Koshland 2018 ; San Martin-Alonso et al 2021 ). As in yeast, the loss of SETX in human cells causes replication stress, making the Fanconi anemia pathway essential for viability ( Said et al 2022 ).…”
Section: Dna–rna Hybrid-unwinding Factors As Potential R-loop Resolvasesmentioning
confidence: 99%